Non-Union in Fractures Neck of Femur in Adults Fixed with Cannuulated Screws (Journal of Pakistan Orthopaedic Association, 2014)
Background: Neck of femur fractures is a devastating injury. Nonunion is one of its main complications. Cannulated screws are now universally used for the fixation of femoral neck fractures.Objective: To determine the frequency of non-union in fracture neck of femur in adults fixed with Cannulated screws.Material and Methods: This descriptive cross sectional study was conducted at orthopedic unit of Ayub Teaching Hospital Abbottabad from 7th March, 2011 to 6th September, 2011 recruiting 113 patients of either gender between 15 to 60 years of age with fracture neck of femur who were fixed with cannulated screws. The data was entered and analyzed with the help of SPSS 10. Results: There were 113 patients with an overall mean age of 43.51 years + 11.94SD. Maximum number of patients was 56 (49.50%) from the age group of 46 to 60 years. Non-union was noted in 16 (14.16%) cases. The maximum number of patients with non-union was 7 (43.75%) in the age group of 46 to 60 years and minimum in the age group of 15 to 25 years i.e. 1 (6.25%).Conclusion: Non-union is high in old ages in displaced fractures of neck of femur treated with cannulated screws.Key Words: Neck of femur fracture, Non-union, Cannulated Screw.